Impact of Internal Financial Factors on Firm Value in Indonesian Manufacturing Firms (2021–2023) - MIRAYANI, Luh Putri Mas; YUESTI, Anik; MAHARANI, Anak Agung Ayu Trisna (PT. Keberlanjutan Strategis Indonesia, 2025)
Purpose:Manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period will be the focus of this study, which seeks to investigate the effect of company value on profitability, debt policy, firm size, firm age, and dividend policy. Firm value is a key measure for investors in assessing company performance and long-term viability. This research is motivated by the volatility in stock prices among manufacturing firms, which raises concerns about the factors that drive firm valuation.Methodology:The study employs an explanatory research design and a quantitative technique. Firm value is measured using the Price to Book Value (PBV) ratio. The independent variables include profitability (ROA), debt policy (DER), firm size (SIZE), firm age (AGE), and dividend policy (DPR). The population consists of 165 manufacturing firms listed on IDX, and 54 firms were selected through purposive sampling, resulting in 162 observations. Using SPSS's multiple linear regression, we analyzed data extracted from yearly financial reports. To make sure the model was valid, we ran the traditional assumption tests (for normalcy, multicollinearity, heteroscedasticity, and autocorrelation) before we tested our hypotheses.Findings:The findings indicate that profitability, debt policy, and business size exert a substantial and favorable impact on firm value. Conversely, company age and dividend policy exhibit no substantial impact. The modified R² value of 0.801 indicates that 80.1% of the variance in firm value is accounted for by the model.Implication:Managers are encouraged to improve profitability, manage debt prudently, and expand operational scale to enhance investor confidence and firm value. Future study may incorporate variables such as company governance and institutional ownership to yield more comprehensive findings.